A systematic review of comorbidity between cerebral palsy, autism spectrum disorders and Attention Deficit Hyperactivity Disorder. (January 2019) - Craig, Francesco; Savino, Rosa; Trabacca, Antonio
Abstract: Objectives: The aim of this systematic review was to examine the incidence and prevalence of comorbidity between Cerebral Palsy (CP), Autism spectrum disorders (ASDs) and Attention-Deficit/Hyperactivity Disorder (ADHD). Methods: We searched for articles indexed in PubMed, EBSCOhost, Scopus, Web of Science and other potentially relevant internet sources using a combination of expressions including "cerebral palsy" AND "autism" OR "ASD" OR "pervasive development disorder" AND "Attention Deficit Hyperactivity Disorder" OR "ADHD". Results: We identified 2542 studies on CP and ASD and 998 studies on CP and ADHD. After screening titles and abstracts and removing duplicated studies, 47 full papers (CP and ASD n = 28; CP and ADHD n = 19) were downloaded and screened for eligibility. Twenty-eight (CP and ASD n = 16; CP and ADHD n = 12) studies were identified in the peer-review literature. Based on this systematic review, ASD and ADHD seem to be more common in people with CP than in the general population, yet the gold standard methods for diagnosing ASD or ADHD are not suitable for children with motor problems. Conclusions: Assessing the occurrence of ASD and ADHD would improve the significant cost of healthcare, therapies, and overall daily living for families with children affected by CP. However, psychometric studies are needed in the future to promote development of measures suitable for individuals with CP. In addition, this review highlights the paucity of peer-reviewed studies investigating the occurrence of ASD and ADHD in children with different CP subtypes or functional abilities, and there are still some open questions about pathogenic mechanisms common to CP, ASD and ADHD. Highlights: The NICE Guideline stresses the importance of investigating the prevalence of ASD and ADHD in CP. The aim of this study was to examine the prevalence of ASD and ADHD in the CP population. ASD seems to be more common in children with CP than in the general population. ADHD shows a higher prevalence in CP than the general population. Recognizing other NDDs might help to develop improved therapies for children with CP.